Menopausal Symptoms in Overweight and Obese Middle Aged Women: A Community Based Study - Ojha, Neebha; Koirala, Poonam; Shrestha, Srijana (Journal of Institute of Medicine Nepal, 2022)
Introduction Overweight and obesity is on the rise globally and women with higher body mass index at midlife have been found to suffer more from menopausal symptoms. This study aims to assess the menopausal symptoms in overweight and obese middle aged women using menopause rating scale (MRS) in the community setting. Methods This descriptive cross-sectional study was conducted at Gokarneswore Municipality in Kathmandu district, from June to December, 2021. Women in the age group of 40-60 years were interviewed regarding the frequency and severity of menopausal symptoms using MRS. The collected data were entered and analyzed in SPSS 25. Results Among the 378 women, 156 (41.3%) were premenopausal, 104 (27.5%) perimenopausal and 118 (31.2%) were postmenopausal women; and 176 (46.6%) were overweight and 87(23.0%) were obese. Overall, 38-68% suffered from different menopausal symptoms. Most of the menopausal symptoms were not significantly different among normal, overweight and obese middle aged women. Urinary symptom was more frequent in obese premenopausal, however the urogenital symptoms were significantly more in normal weight postmenopausal women (p <0.05). The mean MRS score was similar among normal, overweight and obese women, however according to the menopausal status the mean score was significantly higher among perimenopausal and post menopausal women (p <0.001). Conclusion This study showed that among the middle aged women almost half were overweight and one-fourth was obese. Menopausal symptoms were similarly distributed in perimenopausal and postmenopausal women in overweight and obese middle aged women. It is important to assess the obesity and menopausal symptoms, which can be specifically targeted for treatment.